PERANCANGAN SISTEM INFORMASI MANAJEMEN PENJUALAN MUHAMART SMK MUHAMMADIYAH 04 JAKARTA BARAT DENGAN METODE RAPID APPLICATION DEVELOPMENT - Muhammad Prasteyo; Deden Hedin Purnama Binaefsa; Purwanto (Institut Sains dan Teknologi Al-Kamal, 2026)
Muhamart SMK Muhammadiyah 04 Jakarta Barat is a school minimarket used as a learning facility while serving students’ needs such as food, beverages, and uniforms. The predominantly manual sales process leads to issues such as queues during break time, inefficient transaction and stock recording, and limited information for sales monitoring. This study aims to design and implement a web-based Sales Management Information System to support transaction monitoring, stock management, and sales/financial reporting. The system was developed using the Rapid Application Development (RAD) method through requirement planning, user design (prototyping), construction, and cutover phases. The system was modeled using Unified Modeling Language (UML) and implemented using Laravel (PHP), MySQL, and web technologies (HTML and CSS). Functional testing was conducted using black box testing. The results show that the system supports product data management, stock control, sales transactions, and structured reporting. User evaluation using a Likert scale produced an average score of 4.66 (strongly agree), indicating high acceptance and effectiveness in supporting Muhamart operations.